Conceptual Framework for the Mitigation of Accidents on Building Construction Projects - Sani, Mohammed; Dorcas Omolola, Adeagbo; Joseph Jurbe, Molwus (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Globally, the construction sector has recorded poor performance in safety management. Accidents occur frequently during construction work. As a result of accidents, worker’s loss their lives, or sustained different injuries. Also, the project performance in terms of cost, time and quality is grossly affected. This paper is part of an ongoing Ph.D. research aims to develop a Safety management framework for mitigation of accident on building construction sites in Nigeria. The conceptual framework was developed based on a review of literature. The conceptual framework is divided into five parts: Construction projects' hazards, Safety management roles of project stakeholders, interrelationship among stakeholders’ safety management roles, Safety output and Safety outcome. Lastly, the conceptual framework shows that the stakeholders’ roles and their relationship will develop an effective system of safety management for mitigation of accident on building construction sites.